Climate risk country profile Thailand. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This publication synthesizes climate characteristics and projections, vulnerability to natural hazards, sectoral climate change impacts, and adaptation priorities in Thailand.
Keywords: Economic development -- Thailand; Sustainable development -- Thailand; Economic development -- Environmental aspects -- Thailand; Electronic book